Pengaruh Senam Lansia terhadap Keluhan Muskuloskeletal pada Pra Lanjut Usia di Posyandu Telasih V Desa Kragilan Gantiwarno Klaten - Asha Mufida Azizah; Rina Kurnia (Politeknik Kesehatan Kemenkes Surakarta, 2026)
Background: Older adults often experience physical, social, and mental decline, affecting independence in daily activities. In Indonesia, the proportion of older adults (>60 years) has increased, reaching 11.75% in 2023. Physical changes, particularly in the musculoskeletal system, can impair mobility and reduce muscle strength. Elderly exercise is one effort to reduce complaints by increasing synovial fluid, which lubricates joints, relieves pain, and improves body function. Objectives: This study aims to determine the effect of elderly exercise on musculoskeletal complaints among pre-elderly at Posyandu Telasih, Kragilan Village, Gantiwarno, Klaten. Methods: This study is a quantitative study with a Pre-Experimental design using a one-group pre-post test. The sampling technique used was purposive sampling with a total sample of 30 participants. The instrument used was the Nordic Body Map. Elderly exercise was conducted in 8 sessions over 4 weeks. Data analysis was performed using the paired t-test. Results: The findings indicate that all respondents were female (100.0%), with the majority being middle-aged (53.3%). Most respondents had a normal body mass index (43.3%), and musculoskeletal complaints were more common among elderly individuals working as farmers and laborers (33.3%). The paired t-test results showed a Sig. (2-tailed) = 0.000, indicating a p-value < 0.05, which means that elderly exercise significantly affects musculoskeletal complaints in the elderly. Conclusion: There is a significant effect of elderly exercise on musculoskeletal complaints in the elderly at Posyandu Telasih, Kragilan Village, Gantiwarno, Klaten. Keywords: Elderly Exercise, Elderly, Musculoskeletal Complaints.